Pesticide Residues and Associated Public Health Risks in Vegetables from Irrigated Farms Adjacent to Rift Valley Lake Ziway, Ethiopia - Asrat Fekadu Demsie; Girma Tilahun Yimer; Solomon Sorsa Sota (Journal of Food Quality)
The overuse of pesticides has resulted in the accumulation of harmful residues in vegetables, which requires monitoring to assess the risks to human health. This article presents the levels of 35 pesticide residues in 15 composite vegetable samples from irrigated farmlands adjacent to Lake Ziway, Ethiopia, using the QuEChERS extraction method (Quick, Easy, Cheap, Effective, Rugged, and Safe) and then analyzes them using GC-MS. The study also estimated the health risks associated with the consumption of contaminated vegetables in children and adults, including carcinogenic and noncarcinogenic risks. The predominant pesticide residues found in tomatoes were α-endosulfan (0.58 mg/kg), β-BHC (0.04 mg/kg), heptachlor (0.02 mg/kg), and malathion (0.03 mg/kg), all of which were above the safety limits. Similarly, the mean concentration of heptachlor epoxide (0.04 mg/kg) and propargite (0.11 mg/kg) was higher than the allowed levels of the safety limits for onions. The concentration of pesticide residues detected in 10.6% and 7.9% of tomato and onion samples was above the maximum residual limits of the European Commission (EU-MRLs), respectively. Noncarcinogenic health risk estimates show that onion heptachlor epoxide had THQ > 1, indicating the possibility of systemic health risk in both adult and child consumers. The carcinogenic health risk (CHR) showed that heptachlor epoxide in adults and children and only heptachlor in children had CHR > acceptable limit (10−4) for tomato and onion. Therefore, it is critical to raise awareness among stakeholders while simultaneously implementing sound monitoring policy actions to protect the ecosystem and the health of the population in the study area and beyond.